Evaluation of Business Opportunities in Energy Industry in Northwest Russia. Case: CTS Engtec Oy - Vyslovska, Natalia (Kymenlaakson ammattikorkeakoulu, 2012)
The research was commissioned by CTS Engtec Oy, a Finnish engineering, consulting and project management company with international operations. The research focused on 5 regions of the Northwest Russia, namely, Arkhangelsk region, Kaliningrad region, the Republic of Komi, the Republic of Karelia and Murmansk region. The objectives of the research were to describe the factors influencing CTS Engtec’s opportunities in energy industry of the specified regions, evaluate the company’s business opportunities in the energy industry in the regions of interest, and identify potential projects for CTS Engtec in the energy industry of the regions in the Northwest Russia. The basis of the research was a case study. In this research the case study was the search for energy business opportunities for CTS Engtec Oy in Arkhangelsk region, Kaliningrad region, Republic of Karelia, Republic of Komi, Murmansk region in the northwest of the Russian Federation. The case study was based on the mix of qualitative and quantitative evidence. Qualitative evidence was collected based on the criteria for potential investments selection, defined and approved in agreement with CTS Engtec. Quantitative evidence used in the research comprised statistics data in terms of social and economic development, energy production and consumption figures of each region. As a result, a classification of potential projects for CTS Engtec was made based on the above specified qualitative and quantitative data. After a thorough evaluation CTS Engtec’s opportunities in the Northwest Russia energy industry it was possible to conclude that there are business opportunities for the company in the specified regions. This could be explained with the fact that Russia’s energy demand is forecasted a continuous growth while the majority of the energy facilities in the country are obsolescent. A list of concrete projects for CTS Engtec in the regions of the Northwest Russia was made, and suggestions for further research were defined.